Edukasi Personal Hygiene Remaja di SMP Negeri 3 Getasan, Kabupaten Semarang - Mufidaturrosida, Ana; Utaminingtyas, Farida; Latifa, Dewi Nur; Fatimatuszahra, Faaza; Handayani, Nur (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Health-related behaviors should be instilled in children as early as possible. Children are agents of change who can practice what they have learned through personal hygiene activities and share them with their families and peers. Lack of personal hygiene practices, such as washing hands after various activities, can increase the risk of various diseases. Providing understanding to school-aged adolescents is crucial to foster awareness of the importance of maintaining health. The goal of this activity is to increase adolescents’ understanding of personal hygiene so they can maintain their own cleanliness and health and reduce morbidity. This activity method is implemented by delivering material followed by a discussion and question-and-answer session. Evaluation results indicate an increase in adolescents’ understanding of personal hygiene.